New species and records of the genus Trachypeplus Horváth (Hemiptera: Tingidae) from China - Dang, Kai; Guilbert, Eric; Bu, Wenjun (Zootaxa, 2013)
This paper deals with the genus Trachypeplus from China. Nine species of Trachypeplus are treated in this paper, of which three species, namely Trachypeplus depressus sp. nov., Trachypeplus jingae sp. nov., and Trachypeplus parafulgoris sp. nov., are described as new. These nine species are photographed and keyed.